2019
DOI: 10.1371/journal.pone.0225788
|View full text |Cite
|
Sign up to set email alerts
|

Transient effect of melatonin treatment after neonatal hypoxic-ischemic brain injury in rats

Abstract: Melatonin has potential neuroprotective capabilities after neonatal hypoxia-ischemia (HI), but long-term effects have not been investigated. We hypothesized that melatonin treatment directly after HI could protect against early and delayed brain injury. Unilateral HI brain injury was induced in postnatal day 7 rats. An intraperitoneal injection of either melatonin or vehicle was given at 0, 6 and 25 hours after hypoxia. In-vivo MRI was performed 1, 7, 20 and 43 days after HI, followed by histological analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Indeed, many studies have reported the protective effects of melatonin on tissue injuries caused by oxidative stress. These include ischemia/reperfusion induced injuries of brain, lungs, heart, intestine, testes and skeletal muscle as well as hypoxia-caused tissue and organ damages [ 102 , 103 , 104 , 105 , 106 , 107 ]. The protective effects of melatonin are largely associated with its activity on mitochondria.…”
Section: Mitochondria and Melatoninmentioning
confidence: 99%
“…Indeed, many studies have reported the protective effects of melatonin on tissue injuries caused by oxidative stress. These include ischemia/reperfusion induced injuries of brain, lungs, heart, intestine, testes and skeletal muscle as well as hypoxia-caused tissue and organ damages [ 102 , 103 , 104 , 105 , 106 , 107 ]. The protective effects of melatonin are largely associated with its activity on mitochondria.…”
Section: Mitochondria and Melatoninmentioning
confidence: 99%
“…The study characteristics of the remaining 14 studies, 28‐41 which met the inclusion criteria and reported in this meta‐analysis are shown in Table 1. This included six studies with quantitative data made available following data request from corresponding authors 28,29,30,31,36,41 …”
Section: Resultsmentioning
confidence: 99%
“…Neurobehavioral studies were also reported in 3 studies [ 62 , 132 , 140 ], observing improved cognitive performance, learning and memory, motor function, and co-ordination. Berger et al (2019) [ 141 ] reported no overall long-term treatment effect based on brain injury volume, diffusion tensor imaging, histology and functional outcomes however the variability of injury in this model was large. Subgroup analysis revealed fewer animals with severe injury in the melatonin treated group compared to vehicle and the authors reported an absolute risk reduction for severe injury of 38.7%.…”
Section: Melatonin As a Single Agent For The Low Resource Settingmentioning
confidence: 91%